Combination of Genome-Wide Association Study and QTL Mapping Reveals the Genetic Architecture of Fusarium Stalk Rot in Maize - Liu, Shuangshuang; Fu, Jingxiao; Shang, Zhigang; Song, Xiyun; Zhao, Meiai (Frontiers in Agronomy, 2021)
Stalk rot causes significant yield loss in maize worldwide. The breeding of resistant variety is a potential way to effectively control the disease. This study aims to dissect resistance gene of maize stalk rot caused by Fusarium graminearum. An integrated gene mapping method was conducted using a diversity panel of 165 inbred lines and an F2 population from the hybridization of DTMA66 and Huangzao 4. The 165 inbred lines were clustered into four subgroups, of which tropical materials are the majority. Combining DSI index with single nucleotide polymorphisms (SNPs) of Maize 50K chip and 20K via genome-wide association analysis revealed a total of 34 SNPs that were significantly associated with stalk rot (P<0.001). These SNPs were mainly distributed on chromosomes 1, 3, 4, 8 and 10. The SNP loci on chromosomes 4 and 8 were confirmed by the mapped resistant QTLs of stalk rot. And then one candidate gene was identiﬁed on Chromosome 1 by GWAS, which encoded NAC domain-containing protein (GRMZM2G082709). We analyzed by qPCR that the expression of this gene in disease resistant material was significantly higher than that in disease susceptible material. Moreover, another candidate gene GRMZM2G006745 was detected near to the interval of QTL by GWAS. GRMZM2G006745 located on Chromosome 8 was related to DRE-binding protein. This SNPs and candidate genes we identified would provide essential information for resistant gene cloning and molecular breeding of anti-stalk rot variety in maize.